EFEKTIVITAS E-LEARNING PADLET DALAM PEMBELAJARAN MENULIS BAHASA JEPANG (Studi Eksperimen Pada Peserta Magang LPK JLMC Lembang) - Rizki Maulina Handini, - (2021)
This study aims to determine the level of effectiveness of the padlet in the learning process. Effectiveness is seen from the aspect of the mechanism of using padlets and student learning outcomes. The method used in this research is quantative method. The research design used in this study was true experimental design using experimental and control classes. Data collection was obtained through tests and questionnaires aimed at basic level apprentices at LPK JLMC West Java. Based on the results of the analysis, the t value is 2.09> 2.03 and the Sig. (2-tailed) of 0.044 <0.05, it can be concluded that there is a significant difference between the learning outcomes of the experimental class and the control class after treatment in the experimental class with padlet media in learning to write Japanese with the control class using conventional media. Based on the N-Gain score test, the average value for the experimental class was 0.69 which was categorized as quite effective. The results of the questionnaire showed that the use of padlets gave a positive response and was considered efficient. Efficiency can be seen in terms of the time to collect assignments and practice questions as well as the tidiness process in organizing the pile up of learner assignments. On the other hand, the technical constraints found were limited internet coverage and difficulty using several features in the application.